Determinants of domestic consumers’ awareness of water bills - Rita Martins; Patrícia Moura e Sá; Monteiro, H. (1st International Conference on Redrafting Water Governance, 2015)
In the water industry, transparency in the provision of information to end-users by water utilities and regulatory authorities is essential for consumer protection and confidence. Customers’ awareness of price and quantities consumed is necessary to make rational decisions, but also plays an essential role in policy-making that effectively promotes sustainability in resource use. Based on a survey administered to a sample of Portuguese domestic consumers, the current research investigates the determinants of consumers’ awareness of water invoice’s key elements namely the amount paid and quantity consumed. Findings show that consumers have a limited knowledge of their water bills and that their perception on the tariffs and quantities consumed is low but rises for those who submit the meter reading, have higher environmental awareness and a regular contact with the invoices.